Hyperkalemic periodic paralysis and permanent weakness: 3-T MR imaging depicts intracellular 23Na overload--initial results - Amarteifio, Erick; Weber, Marc-André (Radiology, 2012)
PURPOSE: To assess whether myoplasmic ionic sodium (Na+) is increased in muscles of patients with hyperkalemic periodic paralysis (HyperPP) with 3-T sodium 23 (23Na) magnetic resonance (MR) imaging and to evaluate the effect of medical treatment on sodium-induced muscle edema. MATERIALS AND METHODS: This study received institutional review board approval; written informed consent was obtained. Proton (hydrogen 1 [1H]) and 23Na MR of both calves were performed in 12 patients with HyperPP (mean age, 48 years±14 [standard deviation]) and 12 healthy volunteers (mean age, 38 years±12) before and after provocation (unilateral cooling, one calf). 23Na MR included spin-density, T1-weighted, and inversion-recovery (IR) sequences. Total sodium concentration and normalized signal intensities (SIs) were evaluated within regions of interest (ROIs). Muscle strength was measured with the British Medical Research Council (MRC) grading scale. Five patients underwent follow-up MR after diuretic treatment. RESULTS: During rest, mean myoplasmic Na+ concentration was significantly higher in HyperPP with permanent weakness (40.7 μmol/g±3.9) compared with HyperPP with transient weakness (31.3 μmol/g±4.8) (P=.004). Mean SI in 23Na IR MR was significantly higher in HyperPP with permanent weakness (0.83±0.04; median MRC, grade 4; range, 3-5) compared with HyperPP without permanent weakness (0.67±0.05; median MRC, grade 5; range, 4-5) (P=.002). Provocation reduced muscle strength in HyperPP (before provocation, median MRC, 5; range, 3-5; after provocation, median MRC, 3; range, 1-4) and increased SI in 23Na IR from 0.75±0.09 to 0.86±0.10 (P=.004). Spin-density and T1-weighted sequences were less sensitive, particularly to cold-induced Na+ changes. 23Na IR SI remained unchanged in volunteers (0.53±0.06 before and 0.54±0.06 after provocation, P=.3). Therapy reduced mean SI in 23Na IR sequence from 0.85±0.04 to 0.64±0.11. CONCLUSION: 23Na MR imaging depicts increased myoplasmic Na+ in HyperPP with permanent weakness. Na+ overload may cause muscle degeneration developing with age. 23Na MR imaging may have potential to aid monitoring of medical treatment that reduces this overload.